Akseptasi Teologi Pada Kerukunan Umat Islam dan Kristen di Indonesia - Junio Richson Sirait; Hestyn Natal Istinatun (Jayapangus Press, 2022)
Religious harmony is a goal that is difficult for the people to achieve by the government or figures in various countries. All the work that was done has been good. However, the effort has not led to the completeness of what should be done to realize religious harmony. Intolerance is still strong in a pluralistic community environment, such as blasphemy, the closure of houses of worship, the prohibition of religious service, and discrimination against beliefs that are still in minority status. Theology of Acceptance, specifically in Christianity and Islam, can be complementary to all the efforts that have been done before. So, to get maximum results, researchers conduct qualitative research using qualitative-interpretive approaches to get theological acceptance from the understanding of Christianity and Islam. The result of the findings of this study is that religious harmony can occur by implementing fraternal theology.